2019
DOI: 10.3389/fmicb.2018.03270
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Elementary Bodies by the Opportunistic Fungal Pathogen Candida albicans or Soluble β-Glucan, Laminarin, Inhibits Chlamydia trachomatis Infectivity

Abstract: Microbial interactions represent an understudied facet of human health and disease. In this study, the interactions that occur between Chlamydia trachomatis and the opportunistic fungal pathogen, Candida albicans were investigated. Candida albicans is a common component of the oral and vaginal microbiota responsible for thrush and vaginal yeast infections. Normally, Candida exist in the body as yeast. However, disruptions to the microbiota create conditions that allow expanded growth of Candida, conversion to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…was detected in coinfection with these pathogens, the main key questions are formulated. This yeast inhibits growths or the virulence of other pathogens, perhaps providing chemical resources for bacterial survival in the microenvironment, or promoting microorganism dissemination [32]. Our report has some limitations since we designed the panel test with no specific detection of Candida species.…”
Section: Discussionmentioning
confidence: 98%
“…was detected in coinfection with these pathogens, the main key questions are formulated. This yeast inhibits growths or the virulence of other pathogens, perhaps providing chemical resources for bacterial survival in the microenvironment, or promoting microorganism dissemination [32]. Our report has some limitations since we designed the panel test with no specific detection of Candida species.…”
Section: Discussionmentioning
confidence: 98%
“…A study by Kruppa and colleagues demonstrated a novel interaction between Chlamydia trachomatis and C. albicans via the binding of elementary bodies of Chlamydia trachomatis to C. albicans yeast and hyphal forms. This binding was shown to considerably decrease the capacity of Chlamydia trachomatis to infect human cervical epithelial cells, thereby decreasing its disease progression [ 44 ]. In contrast, another study illustrated that biofilms related to VVC may act as a reservoir for Chlamydia trachomatis [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, from the ratio of exposure/binding rate of these bacteria that cause disease and death are still a minority [33]. In many cases, the asymptomatic presence of bacteria is a prerequisite for disease [34,35,36,37,38]. Therefore, we believe that during the invisible carrying of bacteria in the host, genetic factors that promote bacterial adaptation (including viability and reproductive capacity) and the infection are worthy of attention.…”
Section: Discussionmentioning
confidence: 99%